Optimalisasi Pembelajaran Agroteknologi dan Ilmu Hukum Di Perguruan Tinggi Melalui Generative Artificial Intelligence: Sebuah Panduan Praktis - Ahmad Nadhira; Jenda Ingan Mahuli (Universitas Methodist Indonesia, 2024)
The technological revolution based on artificial intelligence (AI) has brought significant changes in the world of higher education, especially in Agrotechnology and Law learning. Generative Artificial Intelligence (GAI), such as ChatGPT, offers various practical solutions to improve learning effectiveness, from providing interactive learning resources to practical simulations. This article examines the optimization of Agrotechnology and Law learning in higher education through the implementation of GAI. With this approach, it is hoped that a more adaptive, personal, and relevant learning process will be created to meet the needs of the digital era. This research was conducted at Tjut Nyak Dhien University, Medan and the Indonesian Community Development University. The research method used is descriptive qualitative. The results of the study are a guide and ethics for the use of AI for students and lecturers that are aligned with the guidelines for the use of generative artificial intelligence (GenAI) in learning in higher education published by the Directorate of Learning and Student Affairs, Directorate General of Higher Education, Research and Technology, Ministry of Education, Culture, Research and Technology in 2024.